World-Making in the Academy: Transnational Scholars Seeking "Home" in Women's, Gender, and Sexuality Studies. (July 2022) - Duncan, Patti; Driskill, Qwo-Li; Mize, Ronald L.; Osei-Kofi, Nana; Shirazi, Mehra
In this roundtable discussion, faculty of color associated with a Women's, Gender, and Sexuality Studies program reflect on our experiences within the academy. As faculty of color connected to the notion of the transnational through our various identities, experiences, family histories, and places of origin, we discuss the various ways we navigate academic spaces. Through an autoethnographic method, we consider our distinct yet overlapping experiences of seeking "home" in the academy.